A feasible strategy of fabricating hybrid drugs encapsulated polymeric nanoparticles for the treatment of gastric cancer therapy. (October 2021) - Li, Heng; Li, Fanglan; Sun, Ying; Li, Yuqiang
Graphical abstract: Highlights: Synthesis of hybrid drugs capsaicin (CAPS) and biotin (BT) encapsulated with nanoparticles. The in vitro cytotoxicity results shows BT/CAPS@PPNPs induced cell death in gastric cancer cells. The morphological variations of BT/CAPS@PPNPs have evaluated by biochemical methods. The cell death of BT/CAPS@PPNPs was confirmed by flow cytometry analysis. Abstract: Chemotherapy of hybrid-drugs has become one of the widely used therapies for the prevention of cancers with promising clinical results. This study aimed to create compostable polymeric nanoparticles (PPNPs) for the codelivery of capsaicin (CAPS) and biotin (BT) and to examine the anticancer activity of the drug delivery mechanism (CAPS/BT@PPNPs) against in vitro and in vivo gastric cancer cells. Because of the insufficiency of double antitumor drugs BT and CAPS compressed in polymer-based bio-degradable nanoparticles, the encapsulation of BT and CAPS antitumor drugs co-loaded with polyethylene glycol and polylactidecoglycolide nanoparticles (PPNPs) is effective. Transmission electron microscopy (TEM) was utilized to investigate the structure of BT@PPNPs, CAPS@PPNPs, and BT/CAPS@PPNPs, as well as their shape and size. Human gastric carcinoma cell lines, such as SGC-791 and NCI-N87, were also induced to apoptosis in vitro by BT/CAPS@PPNPs. Morphologies and cell death were observed using bio-chemical staining methods, AO/EB (acridine orange/ethidium bromide) and Hoechst. Flow cytometry in dual staining was also used to confirm the mechanistic investigations of apoptosis. Overall, this dual drug delivery strategy suggests that BT/CAPS@PPNPs could be used as a new method to increase the efficacy of gastric therapeutics.